ETHICS AND INTEGRITY: CODE OF CONDUCT FOR SCIENTIFIC RESEARCH IN BRAZIL - Fabiana Divina da Silva; Ivânia Vera; Roberta Almeida Elias; Roselma Lucchese; Sara da Costa Fernandes; Sulamita da Silva Lucas (Universidade Federal do Paraná, 2018)
Objective: To present an analysis of the legal mechanisms that guide scientific research in Brazil in ethics, integrity and its related aspects, regarding misconduct in the production of scientific knowledge. Method: Data was collected through documentary research of publications from regulatory agencies that set the standards for scientific research released in the 2010-2017 period. Results: Data analysis generated a chart of Guidelines of Conduct and the Institutions that generated the records. Despite the differences in the documents of the sources investigated, they all agreed on the term "research misconduct". Conclusion: The institutions should carry out preventive and pedagogical actions targeted to scientific research, as well as promote the standardization of the rules of evaluation and punishment of misconduct.